Collision cross sections of large positive fullerene molecular ions and their use as ion mobility calibrants in trapped ion mobility mass spectrometry - Oppenländer, Tobias; Gross, Jürgen H. (Analytical and bioanalytical chemistry, 2024)
Positive-ion laser desorption/ionization (LDI) of fullerenes contained in soot as produced by the Krätschmer-Huffman process delivers a wide range of fullerene molecular ions from C56+• to above C300+•. Here, the collision cross section (CCS) values of those fullerene molecular ions are determined using a trapped ion mobility-quadrupole-time-of-flight (TIMS-Q-TOF) instrument. While CCS values in the range from C60+• to C96+• are already known with high accuracy, those of ions from C98+• onward had yet to be determined. The fullerene molecular ions covered in this work have CCS values from about 200 to 440 Å2. The fullerene molecular ion series is evenly spaced at C2 differences in composition, and thus, small CCS differences of just 2.2-3.5 Å2 were determined across the entire range. Fullerene M+• ions may be employed as mobility calibrants, in particular, when very narrow 1/K0 ranges are being analyzed to achieve high TIMS resolving power. In addition, due to the simple elemental composition, M+• ions of fullerenes could also serve for mass calibration. This study describes the determination of CCS values of fullerene molecular ions from C56+• to C240+• and the application of ions from C56+• to C220+• to calibrate the ion mobility scale of a Bruker timsTOFflex instrument in any combination of LDI, matrix-assisted laser desorption/ionization (MALDI), and electrospray ionization (ESI) modes in the CCS range from about 200 to 420 Å2. This use was exemplified along with ions from Agilent Tune Mix, leucine-enkephalin, angiotensin I, angiotensin II, and substance P.
Gesehen am 01.04.2025